Influence of Repeated Crops, Predecessors and Differentiated Use of Mineral Fertilizers on the Yield of Winter Wheat (In Conditions of Typical Sierozem Soils Committed Irrigation Erosion) - Bobur Mansurovich Kholmurzaev (Zien Journals, 2022)
Based on the results of the study, criteria for the selective introduction of suitable secondary crops (beans, mung bean, soybeans) and perennial alfalfa and mineral fertilizers were selected, which reduce the negative effects of irrigation erosion, increase soil fertility, and ensure the production of high-quality grain from winter wheat. The results show that, after repeated crops, the volume mass of the 0-30 cm layer of soil is 0.03-0.05 g / cm3 less than in the case of unwashed soils compared to the initial value, the porosity is 1.9- 2.5% higher, in heavily washed soils respectively 0.02-0.04 g / cm3 less and 1.7-2.3% higher, compared to the control of soil water permeability 38.3-51.2 m3 / ha and at the end of the period of application 24.9-42.7 m3 . Grain yield in unwashed varieties under the influence of repeated crops and mineral fertilizers (N150P105K75 kg / ha), providing favorable conditions for full germination, growth and development of winter wheat seeds (92.3-91.5%), providing grain yield in unwashed soil variants (68.8-72.4 c / ha), protein content from 14.8-15.6 and gluten 31.8-32.4%, mineral fertilizers (N180P126K90 kg / ha) after repeated sowing of the above in areas with strongly washed soils in the applied variants are 69.2-74.5 с / ha, 15.2-15.8 and 32.1- 32.8%, respectively, plays an important role in ensuring food security of the population during the current coronavirus pandemic
Keywords: typical seirozem; irrigation erosion; fertility; grain yield